THE COMPARATIVE STUDY BETWEEN THE EFFECT OF COVID-19 AND EARTHQUAKE DISASTER ON TOURISM ATTRACTION IN YOGYAKARTA - Prakoso, Yohanes Meindra; Ramadhika, Boris (Institut Pariwisata dan Bisnis Internasional, 2020)
COVID-19 and earthquake disaster both give effect in Tourism Attraction, then in this study will compare the difference impact between COVID-19 and earthquake disaster, especially in Yogyakarta. This study deals with the hospitality industry condition during Corona Virus Disease (COVID-19) and earthquake disaster in Yogyakarta 2006. This study is to seek an answer to these two research questions: 1. What is the effect of the COVID-19 virus on Tourism Attraction in Yogyakarta? 2. Is the impact of the COVID-19 virus on Tourism attractions in Yogyakarta has a more severe impact than an earthquake in 2006? From the results of this study, it was found that COVID-19 is more dangerous than earthquakes, particularly in the economy sector. The method used in this study is a descriptive qualitative method; the problem that can be investigated by qualitative descriptive research refers to quantitative studies, comparative studies (comparisons). The data to support this study was taken from journals, books, websites, government documents, and any other sources or articles.